Genjer Extract As An Alternative Preventing Constipation In Pregnancy - Rusmiati; Titin Eka Sugiatini (Lembaga Pengembangan Kinerja Dosen, 2023)
Background : Constipation is a problem that is always disturbing in pregnant women, in general trimester pregnant women 3. Constipation is a difficult condition or unable to defecate, hard stool, a sense of defecation is not complete (there is a sense of wanting to defecate but unable to remove it) accompanied by complaints of the stomach feeling full and bloating. If this problem is left alone it will have an impact on the process of childbirth and childbirth. Objectives : The purpose of this study can be seen the effect of giving genjer extract as an alternative to prevent constipation during pregnancy at PMB Rusmiati Karang Tengah Tarumajaya Research Methods : This research design uses the quasi-experimental study method with pretest-posttest with control group design with a total of 32 respondents. The technique used in this study is a saturated sample. Results : The results of the study were found that after consuming the genjer extract of pregnant women who experience constipation into non-constipation it is shown in the occurrence of chapters for 2 weeks in pregnant women to normal. Conclusion : There is an effectiveness of the effect of providing genjer extract consumption as an alternative to prevent constipation during pregnancy.